Mecanismos associados à atividade antiproliferativa de derivados n-acilidrazônicos sobre linhagens derivadas de carcinoma hepatocelular - Silva, Guilherme Álvaro Ferreira Da (2021)
Liver cancer is the second leading cause of cancer death among men, with hepatocellular carcinoma (HCC) being the most commonly diagnosed primary liver cancer. Regardless of the introduction of new therapeutic modalities for HCC advanced-stage (target-directed therapies and immunotherapy), mortality rates remain high. The ineffectiveness of the treatment is generally associated with primary or acquired resistance of tumor cells to available drugs. Therefore, it is relevant to identify new drugs with antitumor activity to improve the therapeutic arsenal for HCC. It is known that selective inhibitors of histone deacetylases (HDACs) can be useful as antineoplastic agents. In a previous study, N-acylhydrazonic derivatives were obtained (LASSBio-1909, 1911, 1935 and 1936) with the proposal of acting as selective inhibitors for HDACs 6/8. In this way, the aim of the present study was to evaluate the anti-proliferative potential of these substances on HCC-derived cell lines and to investigate the mechanisms of action of the most active compound. The results showed that NAH derivatives (mainly LASSBio-1911 and 1935) effectively inhibited the proliferation and induced cell death in the HepG2 and Hep3B cell lines. Furthermore, the substances were selective for tumor cells when compared to normal cells. LASSBio-1911 induced cell cycle arrest at the G2/M transition which was associated with its ability to cause DNA damage and activate the G2/M checkpoint. Increased levels of expression of CDKN1A (p21) and sustained activation of ERK were observed in cultures of HepG2 and Hep3B treated with LASSBio-1911. The substance LASSBio-1911 induced apoptosis in HCC cell lines, and this activity was more expressive on HepG2 when compared to Hep3B. The pro-apoptotic activity was correlated with an increase in the Bax/Bcl-2 ratio in both cell lines. Moreover, LASSBio-1911 inhibited the migration capacity and induced senescence in Hep3B. The data here presented show that LASSBio-1911 has promising antitumor activity against HCC. The effects of this substance on the proliferative and migratory behavior of the HepG2 and Hep3B cell lines were correlated with the inhibition of HDAC6, since there was a significant increase in the expression of acetylated alpha-tubulin, an important target of HDAC6. Therefore, we demonstrate that inhibition of HDAC6 is a promising strategy for HCC treatment.